Assessing Cancer Risk Associated with Aquatic Polycyclic Aromatic Hydrocarbon Pollution Reveals Dietary Routes of Exposure and Vulnerable Populations. (19th September 2018) - Gearhart-Serna, Larisa M.; Jayasundara, Nishad; Tacam, Moises; Di Giulio, Richard; Devi, Gayathri R.
Abstract : Polycyclic aromatic hydrocarbon (PAH) exposure is widespread, and many PAHs are considered carcinogenic. The PAH-contaminated AWI Superfund site in Virginia provides a model for studying a complex PAH mixture and its extrapolation to cancer risk and PAH exposure in the general population. We examined cancer risk at the Superfund site due to sediment-derived PAHs and then evaluated PAH sources in the general population and potentially vulnerable subpopulations upon PAH mixture exposure. The PAH mixture was assessed for potential carcinogenicity using the US EPA's OncoLogic™ ranking tool and the US EPA list of priority PAHs. Cancer risk due to PAH exposure was calculated for Superfund site users and compared to the US EPA assessment. Human intake and health endpoints of PAHs within the mixture were extracted from USEtox® chemical fate database, while mean intake exposure was calculated for U.S. adults for select PAHs using NHANES database urinary biomarkers. Eleven PAH compounds within the mixture were of carcinogenic concern, and seven PAHs conveyed significant excess cancer risk at the Superfund site and in the general population, wherein PAH-contaminated seafood ingestion was a main contributor. Other dietary sources of PAHs derived from PAH-contaminated soil or water could also play a role in total exposure. Vulnerable populations to PAH exposure and coinciding increased cancer risk may include, in addition to smokers, children and non-Hispanic blacks, which is a public health concern.